The Impact of Marketing Mix Strategy for Fruit Salad Sales in Blora - Ramasari, Aulia; Victor Sitepu, Hans (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
This study delves further into the impact of marketing mix methods on growing fruit salad sales in Blora. This study is inspired by the large number of similar business competitors who may reduce the quantity of consumers. The method utilized in this analysis is a qualitative descriptive approach, which aims to portray reality by using an entrepreneur's experiences to describe current problems. The goal of this research is to determine whether utilizing the proper and efficient marketing strategy will promote higher product sales, as well as to provide an overview of how to utilize the right marketing mix in product sales. Based on the study's findings, it is clear that when starting a firm, it is critical to focus on the correct marketing strategy, such as employing a marketing mix that incorporates product, pricing, promotion, and place strategies. Selecting an appropriate plan can boost revenue. To empirically validate the findings of this study, more research employing quantitative data is expected in the near future